Legal Effort Undertaken by Notaries in Restoring Their Good Name From Sanctions Imposed by The Notaries Supervisory Council - Rizqi, Adella Fania; Arifulloh, Achmad; Widayati, Widayati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. As a public official in the preparation of authentic deeds, a notary public has a role in ensuring certainty, order, and legal protection in the preparation of deeds as regulated in the Notary Public Law and other laws and regulations. However, in carrying out their duties, a notary public is under the supervision of the Notary Supervisory Board. If proven to have violated statutory provisions or the code of ethics, they will be subject to sanctions such as verbal warnings, written warnings, temporary dismissal, or dishonorable dismissal. This study aims to analyze the forms of legal efforts that a notary can take to restore his good name, as well as to examine the effectiveness of these recovery mechanisms within the framework of legal protection for notaries. This research uses a normative juridical approach with a case study approach and analysis of applicable laws and regulations, particularly the Notary Law and its implementation. Data obtained using literature studies obtained from secondary data on legal literature, court decisions, and documents related to the preparation of this scientific work, and the analysis in this study is perspective. The results of the study indicate that legal remedies that can be taken include administrative objections, appeals to the Notary Honorary Council, and lawsuits to the State Administrative Court. However, there are still challenges in its implementation, such as a lack of transparency and accountability in the supervisory process and the less than optimal restoration of good name both formally and socially. Therefore, it is necessary to strengthen regulations and legal protection mechanisms that are more in favor of the principles of justice and the human rights of Notaries as citizens.